2022
DOI: 10.1038/s41598-021-03830-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cerebral blood flow, oxygenation and cytochrome c oxidase stability in preterm infants during the first 3 days after birth

Abstract: A major concern with preterm birth is the risk of neurodevelopmental disability. Poor cerebral circulation leading to periods of hypoxia is believed to play a significant role in the etiology of preterm brain injury, with the first three days of life considered the period when the brain is most vulnerable. This study focused on monitoring cerebral perfusion and metabolism during the first 72 h after birth in preterm infants weighing less than 1500 g. Brain monitoring was performed by combining hyperspectral ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Longitudinal neurometabolic optical monitoring has elucidated risk factors for hypoxic–ischemic brain injury in several pediatric contexts, including during birth transition in healthy and high-risk neonates [ 220 , 234 240 ], and during generalized seizures [ 241 , 242 ], cardiac surgery requiring cardiopulmonary bypass [ 213 , 225 , 243 , 244 ], and extracorporeal membrane oxygenation support [ 226 , 245 ]. Quantification of oxygen delivery to the brain intra-arrest [ 246 ] (Fig.…”
Section: Advances In Neuromonitoringmentioning
confidence: 99%
“…Longitudinal neurometabolic optical monitoring has elucidated risk factors for hypoxic–ischemic brain injury in several pediatric contexts, including during birth transition in healthy and high-risk neonates [ 220 , 234 240 ], and during generalized seizures [ 241 , 242 ], cardiac surgery requiring cardiopulmonary bypass [ 213 , 225 , 243 , 244 ], and extracorporeal membrane oxygenation support [ 226 , 245 ]. Quantification of oxygen delivery to the brain intra-arrest [ 246 ] (Fig.…”
Section: Advances In Neuromonitoringmentioning
confidence: 99%
“…Furthermore, the algorithm can be modified to recover other chromophores by increasing the number of chromophores in the fitting parameters and changing the wavelength region of interest to cover the spectral range of the target chromophores. Notably, future work will include adapting the algorithm to monitor the redox state of Cytochrome C Oxidase (CCO), a key biomarker of cerebral oxidative metabolism ( Rajaram et al, 2018 , 2022 ; Lange et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the potential clinical utility of DCS-based CBF analysis in extremely preterm infants, with the reports of distinctive fluctuating patterns in CBF between days 1 and 3 of life 16 and significantly reduced CBF in the presence of low-grade IVH 8 . However, additional research is required to evaluate the clinical utility of DCS monitoring in the context of impaired CAR and IVH vulnerability in ELGA infants.…”
Section: Introductionmentioning
confidence: 99%